FTIR studies of annealing processes and irradiation effects at 266 nm in ozone-amorphous ice-mixtures: Low-Temperature Physics and Chemistry in Cryomatrice - Chaabouni, H.; Schriver-Mazzuoli, L.; Schriver, A. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2000)
Fourier Transform Infrared (FTIR) Spectroscopy is used to study the vibrational spectroscopy of ozone trapped in amorphous ice (a situation observed on icy satellites in the solar system). Evaporation of ozone from ice is investigated from 30 to 150 K under a static pressure of 10√7 Torr. Condensed and chemisorbed ozone on the surface of micropores is released at a temperature between 40 and 80 K, and ozone in water lattice evaporates starting from 120 K. The release of ozone probes the gradual transformation of water ice. The photochemistry of ozone in excess ice is also investigated using 266 nm laser irradiation. At low temperature, condensation of mixtures H2 O/O3 leads to ozone trapped in pores and cavities, and H2O2 is produced through the hydrogen bonded complex between ozone and free OH bonds. At higher temperature, when a solid solution of ozone in water is observed, H2O2 is formed by the reaction of the excited oxygen atom O(1D) with the nearest water molecules. Kinetic studies suggest that recombination of the dioxygen molecule with ground-state atomic oxygen O(3P) is a minor channel.